Your answer is the third one. WHen it comes to system of equations, this will cancel out 4a, therefore isolating the variable. That turns the equation into -2b=-5.
<h3><u>(1 + 5y)(1 - 5y) is the fully factored form of this polynomial.</u></h3>
This polynomial can be factored using difference of squares.
This polynomial is in the form of a^2 - b^2 = (a + b)(a - b)
Because 1 * 1 = 1, we can use this formula to simplify this polynomial.
1 - 25y^2 = (1 + 5y)(1 - 5y)
We can use FOIL to verify this.
(1 + 5y)(1 - 5y)
1 - 5y + 5y - 25y^2
1 - 25y^2
Answer:
B
Step-by-step explanation:
Substitute the following values into the cylindrical volume equation below:
r= 30/2 = 15 cm
h = 320 cm
V=πr2h
V=(3.14)(15)^2 (320)
V=226 080 cm^3